Would Cortisol Measurements Be a Better Gauge of Hydrocortisone Replacement Therapy? Congenital Adrenal Hyperplasia as an Exemplar - Peter C Hindmarsh; John W Honour (International Journal of Endocrinology)
There is an increase in mortality and morbidity as well as poor quality of life in patients with congenital adrenal hyperplasia (CAH) and other causes of adrenal insufficiency. Glucocorticoid replacement therapy should aim to replace the missing cortisol as close as possible to the normal circadian rhythm using hydrocortisone. Dosing should be based on the individual’s absorption and clearance of the drug. Adequacy of dosing should be checked using 24-hour profiles of plasma cortisol with samples drawn preferably every hour or at least every 2 hours. Measurement of cortisol should be the preferred method of assessing replacement therapy as it is over- and undertreatment with hydrocortisone, both of which can occur over a 24-hour period, which leads to the problems observed in patients with CAH and adrenal insufficiency.